Efficacy of Traditional Chinese Exercise in Improving Gait and Balance in Cases of Parkinson's Disease: A Systematic Review and Meta-analysis - Wu, Minmin; Tang, Qiang; Wang, Linjing; Zhang, Mei; Song, Wenjing; Teng, Lili; Zhu, Luwen (Frontiers in Aging Neuroscience, 2022)
Background: The efficacy of traditional Chinese exercise (TCE)-based intervention in the improvement of motor function in patients with Parkinson’s disease (PD) is controversial. The present study aimed to assess the effects of TCE on balance and gait outcomes, as well as motor symptoms in individuals with PD, and evaluate potential discrete moderators such as TCE dosage-related variables. Method: PubMed, Embase, Cochrane's Library, Web of Science, Medline, and Scopus were systematically searched from their dates of inception to February 2022. All studies were randomized controlled trials (RCTs) of TCE-based interventions for PD. The treatment effects were estimated using a random-effect meta-analysis model with standardized mean differences (Hedges' g). The Physiotherapy Evidence Database was used to evaluate the methodological quality of the study. Result: Fifteen studies involving a total of 873 participants were included in the final analysis. The meta-analytic findings revealed significant improvements in balance outcomes [Berg Balance Scales(BBS) (g= 0.83, 95% CI= 0.37−1.29, p=0.000, I2=84%), time up and go (TUG) (g= −0.80, 95% CI= −1.13 to −0.47, p=0.000, I2=81%), and the one legged blind balance test (g= 0.49, 95% CI= 0.13−0.86, p=0.01, I2=10%)], as well as gait outcomes [gait velocity ( g= 0.28, 95% CI= 0.02−0.54, p=0.04, I2=64%), 6-minute walking test (6MWT) (g=0.32, 95% CI 0.01−0.62, p=0.04, I2=15%), stride length (g=0.25, 95% CI=0.08−0.41, p=0.003, I2=42%)], and motor symptoms [Unified Parkinson’s Disease Rating Scale part III(UPDRS-III) (g= −0.77, 95% CI= −1.06 to −0.48, p= 0.000, I2=76%)]. However, cadence (g= −0.03) and step length (g= 0.02) did not differ significantly. The moderator shows that the effects of TCE on BBS and gait velocity were moderated by Pedro score, exercise type, control group type, and number of sessions. Meta-regression found that TCE (exercise duration, number of sessions, and session duration) was significantly associated with improved UPDRS-III and BBS scores. Conclusions: These findings provide evidence for the therapeutic benefits of TCE as an adjunct therapy for patients with PD. TEC dosage (high-intensity long sessions) may moderate some favorable effects.